ANALISIS PENGELOLAAN PELABUHAN PERIKANAN PANTAI TASIKAGUNG KABUPATEN REMBANG UNTUK PENINGKATAN PRODUKSI PERIKANAN TANGKAP - Nugraheni, Hestyavida; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2013)
The increased of fisheries production was supported by an increased the number visits of ships in PPP Tasikagung. Increased of its should be balanced with good management of PPP Tasikagung. This research objective was to determine the condition facilities in PPP Tasikagung, knew the managements of activities and facilities in PPP Tasikagung, and analyzed appropriate strategies to be applied in the management of PPP Tasikagung which was expected to provide useful output for all aspects of PPP Tasikagung. The method used in this research was descriptive by SWOT analyzed was identified the various factors in order formulated a strategy for the proper management. The results showed that the existing facilities at the Coastal Fishery Port of Tasikagung was still a good physical condition and was still proper to used, as good as that activities from landed fish, fish processed, until marketing the fish was good work, problem only occurred in the absence of cold storage facility and hygienic TPI. While the results obtained from the application of SWOT analysis was S-O strategy (Strength-Opportunity) in its application used force to take advantage of an opportunity.